Software tools for learning artificial intelligence algorithms - Stamenkovic, Srecko; Jovanovic, Nenad; Vasovic, Bojan; Cvjetkovic, Milos; Jovanovic, Zoran (The Artificial intelligence review, 2023)
In recent years, artificial intelligence has become an important discipline in the field of computer science. Students, in the absence of basic prior knowledge, may have difficulty tracking materials when they first encounter complex and abstract artificial intelligence algorithms. Numerous researchers and educators point out that the use of simulation systems and software tools to illustrate the dynamic behavior of the algorithm can prove to be an effective solution. The introduction and adoption of new technologies in learning and teaching has evolved rapidly. This conceptual review paper aims to explore the emergence of innovative educational technologies in the teaching and learning of artificial intelligence. The aim of this paper is to analyze the existing representative educational tools for learning topics in the field of artificial intelligence to highlight their characteristics and areas they cover, so that readers can more easily draw conclusions about the possible use of some of the analyzed systems.